Protein Kinase Cα (PKCα) Acts Upstream of PKCθ To Activate IκB Kinase and NF-κB in T Lymphocytes - Trushin, Sergey A. (American Society for Microbiology, 2003)
NF-κB is an ubiquitous transcription factor that is a key in the regulation of the immune response and inflammation. T-cell receptor (TCR) cross-linking leads to NF-κB activation, an IκB kinase (IKK)-dependent process. However, the upstream kinases that regulate IKK activity following TCR activation remain to be fully characterized. Herein, we demonstrate using genetic analysis, pharmacological inhibition, and RNA interference (RNAi) that the conventional protein kinase C (PKC) isoform PKCα, but not PKCβ1, is required for the activation of the IKK complex following T-cell activation triggered by CD3/CD28 cross-linking. We find that in the presence of Ca(2+) influx, the catalytically active PKCαA25E induces IKK activity and NF-κB-dependent transcription; which is abrogated following the mutations of two aspartates at positions 246 and 248, which are required for Ca(2+) binding to PKCα and cell membrane recruitment. Kinetic studies reveal that an early phase (1 to 5 min) of IKK activation following TCR/CD28 cross-linking is PKCα dependent and that a later phase (5 to 25 min) of IKK activation is PKCθ dependent. Activation of IKK- and NF-κB-dependent transcription by PKCαA25E is abrogated by the PKCθ inhibitor rottlerin or the expression of the kinase-inactive form of PKCθ. Taken together, our results suggest that PKCα acts upstream of PKCθ to activate the IKK complex and NF-κB in T lymphocytes following TCR activation.